2017
DOI: 10.1037/pha0000147
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management targeting abstinence is effective in reducing depressive and anxiety symptoms among crack cocaine-dependent individuals.

Abstract: Although contingency management (CM) is effective in promoting abstinence and treatment retention among crack cocaine users who meet the criteria for cocaine dependence, less is known about its off-target effects. In this secondary analysis, we evaluated the impact of CM on depressive and anxiety symptoms in a sample of cocaine-dependent individuals under treatment. Sixty-five crack cocaine users who met the criteria for cocaine dependence were randomly assigned to receive 12 weeks of standard treatment alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…The high quantity and frequency of crack use reported by the participants, together with the fact that most of them reported having used crack continuously for more than 10 years and the evidence of numerous failed treatment attempts, highlight the severe, compulsive, and chronic nature of this disorder. Those findings also indicate the lack of efficacy of the existing centers in treating crack dependence and advocate for the need to incorporate evidence-based treatments such as contingency management (Miguel et al 2016 Miguel et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…The high quantity and frequency of crack use reported by the participants, together with the fact that most of them reported having used crack continuously for more than 10 years and the evidence of numerous failed treatment attempts, highlight the severe, compulsive, and chronic nature of this disorder. Those findings also indicate the lack of efficacy of the existing centers in treating crack dependence and advocate for the need to incorporate evidence-based treatments such as contingency management (Miguel et al 2016 Miguel et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Co-occurring psychiatric disorders are highly prevalent among individuals with CUD and represent a severe burden with direct impact on how individuals feel and function in their daily lives (Conner et al, 2008;Conway et al, 2006;Ford et al, 2009;Grant et al, 2004). Nonetheless, only a few treatment trials for CUD have found improvements in psychiatric symptoms (Miguel et al, 2017;Petry et al, 2013). This is possibly due to the fact that most treatment trials for CUD do not directly target psychiatric symptoms and thus treatment effects for this outcome tend to be less robust.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group published the first Brazilian CM treatment trial for CUD using the classic vouchers-based, escalating reinforcement type of approach for the application of CM (Miguel et al, 2016(Miguel et al, , 2017(Miguel et al, , 2018(Miguel et al, , 2019. Despite our positive results, we observed specific components of the CM approach that could be generating unnecessary costs and limiting the efficacy and treatment engagement potential of CM.…”
Section: Introductionmentioning
confidence: 77%